KEBERHASILAN IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 71 TAHUN 2010 TENTANG STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL - RAMLI, MUHAMMAD; AFRIWAN, OKKY; BUDIARTO, BUDIARTO (Universitas Mahasaraswati Mataram, 2020)
This study aims to determine the factors that play a role in the successful implementation of Government Regulation Number 71 of 2010 concerning Accrual Based Government Accounting Standards. This type of research is a quantitative research with a regression analysis method to the factors of regulation, HR, commitment, supporting tools, and relevant training which are thought to influence the successful implementation of Government Regulation No.71 of 2010 concerning Accrual Based Government Accounting Standards. The research population is the regional financial manager in 33 Regional Apparatus Organizations/Regional Apparatus Work Units within the Mataram City Government, namely the Head of the OPD/SKPD and/or Financial Administration Officials, Treasurers and Planning Staff. The research sample is selected by using the purposive sampling method with 91 respondents out of 99 respondents who are given questionnaires. The results showed that partially the quality of human resources and training have a significant relationship, while regulations, commitments, and supporting instruments do not have a significant relationship to the success of the local government in implementing PP71/2010. And based on simultaneous analysis shows that there is an influence of the relationship between regulations, human resources, commitments, supporting tools, and training on the success of local governments in the implementation of PP71/2010.